2021
DOI: 10.1177/17562848211042185
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of clinical outcomes of COVID-19 patients undergoing gastrointestinal endoscopy

Abstract: Background: The impact of gastrointestinal endoscopy on COVID-19 infection remains poorly investigated. We herein performed a systematic review and meta-analysis to evaluate the outcomes of COVID-19 in patients undergoing gastrointestinal endoscopy. Method: Ovid Medline, Ovid EMBASE, Ovid the Cochrane Library, and other electronic databases were searched until 30 November 2020 to identify publications with confirmed COVID-19 infection in patients undergoing gastrointestinal endoscopy. The primary outcomes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Accordingly, a multicenter study confirmed our local findings showing a minimal infection rate in a lockdown situation with provision of personal protective measures. 24 , 25 During the pandemic, we were able to comply with ESGE recommendations 26 to establish a negative pressure room with laminar air flow for endoscopy. However, during the entire pandemic, it was actually used only twice, as we had an internal agreement permitting us to perform endoscopies in positive patients at the ICU, if possible only with an emergency indication.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a multicenter study confirmed our local findings showing a minimal infection rate in a lockdown situation with provision of personal protective measures. 24 , 25 During the pandemic, we were able to comply with ESGE recommendations 26 to establish a negative pressure room with laminar air flow for endoscopy. However, during the entire pandemic, it was actually used only twice, as we had an internal agreement permitting us to perform endoscopies in positive patients at the ICU, if possible only with an emergency indication.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, according to a recent systematic review and meta‐analysis regarding the clinical outcomes of COVID‐19‐positive patients undergoing gastrointestinal endoscopy, the risk of SARS‐CoV‐2 transmission within gastrointestinal endoscopic units is considerably lower if proper PPE is utilized. Additionally, low fatality and complication rates, and a high procedural success rate for diverse gastrointestinal endoscopic procedures, have been demonstrated in COVID‐19‐positive Western cohorts 3 …”
Section: Figurementioning
confidence: 99%
“…The causative agent—severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)—is a virus mainly transmitted via droplets and contact; however, data are emerging that support airborne transmission during aerosol‐generating procedures, including endoscopy. Since almost 50% of COVID‐19 patients exhibit detectable viral RNA in fecal samples, 1,2 there are still considerable concerns regarding viral transmission within endoscopic units, forcing endoscopists to implement strict precautions, such as a high threshold for endoscopy 3 . Indeed, the pandemic has had a significant global impact on endoscopic services, which is linked to the substantial reduction in capacity 4 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth noting that this mouthpiece is designed to reduce the gag reflex. The COVID-19 pandemic has had a major impact on upper gastrointestinal endoscopy practices worldwide [ 3 , 4 ]. In upper gastrointestinal endoscopy, aerosol-generating procedures are performed at close range, raising concerns about the inadvertent exposure of healthcare workers and the possibility of infection [ 5 , 6 ].…”
mentioning
confidence: 99%